CERTAIN ISSUES REGARDING THE CAUSES AND CONDITIONS OF CRIMES (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
the article talks about the causes and conditions of offenses and highlights the consequences of committing them by minors, women and other citizens. It was also emphasized that young people should spend their free time productively, and involve them in various activities aimed at increasing their legal awareness and culture.